Foreword: Biology/embodiment/desire. Issue 2 (3rd April 2018) - Terry, Jennifer; Willey, Angela
ABSTRACT: The sexological roots of "lesbian" and the "queer" turn from biologized categories of sexual difference pose an exciting set of questions and tensions for thinking about queer feminism and biological meanings. This issue seeks to open space to explore how we might reconcile assumptions about "female same-sex sexuality" that often accompany "lesbian" with queer and trans-feminist treatments of science, embodiment, and desiring, while at the same time insisting on the importance of an undertheorized dyke legacy for thinking the at-once material and political nature of sexuality.